Impact of Obesity on Serum Levels of Neuropeptide –Y in Type 2 Diabetics in Relation to Glycemic Status - Nada T Hasan; Shatha Ali (Iraqi Journal of Pharmaceutical Sciences, 2025)
Obesity by multiple mechanisms can contribute not only to the development of type 2 diabetes mellitus (T2DM) but also by further worsening the patient’s condition. One of these mechanisms may include the disturbances of neuropeptide Y (NPY) serum level which is one of the most powerful orexigenic peptides, that’s produced in large amounts in the hypothalamus, as well as in peripheral adipose tissue. The present study aimed to assess the impact of obesity in type 2 diabetic patients on serum neuropeptide-Y level and its impact on fasting serum glucose and insulin levels. Eighty-seven T2DM patients attending the clinic of The National Center of Diabetes Treatment & Research/Baghdad, were included in this study, had been categorized into; Group (1): 45 patients (19 male, 26 female) obese T2DM patients with BMI (30.5- 44) kg/m2 and age range (31-59) years, and Group (2): Normal body weight T2DM patients with BMI (18.6-24.9) kg/m2, included 42 patients (20 male, 22 female), with age range of (33-60) years .Fasting blood specimens were utilized to measure serum NPY and glycemic markers. Data analysis revealed that fasting serum glucose, HbA1c, homeostatic model assessment of insulin resistance (HOMA-IR) and neuropeptide Y values were significantly elevated (P˂0.001) in group-1 in comparison with group-2, however fasting insulin level and homeostasis model assessment of beta-cell function (HOMA-B) were significantly elevated (P˂0.001) in group-2 compared to group-1. Furthermore, neuropeptide-Y was positively correlated with BMI (rho=0.670, P˂0.001), fasting serum glucose (rho=0.697, P˂0.001), HbA1c% (rho=0.274, P=0.010) and HOMA-IR (rho=0.301, P=0.005), whereas it was negatively correlated with fasting serum insulin (rho=-0.296, P=0.005) and HOMA-B (rho=-0.598, P˂0.001).